2017
DOI: 10.1108/et-10-2015-0094
|View full text |Cite
|
Sign up to set email alerts
|

The employability skills of business graduates in Syria

Abstract: Purpose The purpose of this paper is to compare the desired employability skills of business graduates in Syria from the perspective of both higher education policymakers and employers in the private sector. Design/methodology/approach Interviews were conducted with 12 higher education policymakers and managers from the business sector. Content analysis was utilized to analyse the content of the interviews and the strategic priorities of the higher education sector in Syria. Findings Results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 55 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…First, the findings suggest that students should be provided with a deeper understanding of skill requirements to proactively complement their academic qualifications, which would resemble a skills development process. Moreover, the findings imply that universities should steadily and consistently teach appropriate skills in cooperation with employers by opening career and job centres to facilitate placement for graduating students (Ayoubi et al., 2017). Besides, universities must improve course curricula regularly by incorporating graduate employability skills and labour market dynamics in collaboration with industries, managers, and faculties to improve outcomes (Pheko & Molefhe, 2016).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the findings suggest that students should be provided with a deeper understanding of skill requirements to proactively complement their academic qualifications, which would resemble a skills development process. Moreover, the findings imply that universities should steadily and consistently teach appropriate skills in cooperation with employers by opening career and job centres to facilitate placement for graduating students (Ayoubi et al., 2017). Besides, universities must improve course curricula regularly by incorporating graduate employability skills and labour market dynamics in collaboration with industries, managers, and faculties to improve outcomes (Pheko & Molefhe, 2016).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…University graduate employability is an important challenge for many countries, including developing countries like Bangladesh (Asonitou, 2015). To address these challenges, it is essential to identify critical graduate skills and the challenges faced by graduates (Abbasi et al., 2018; Ayoubi et al., 2017). However, there is a widespread gap between the skills of graduates and those demanded by employers, which raises concerns about students’ capacity to smoothly transition to the workforce (World Economic Forum, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that enhancing the employability skills of recent MBA graduates will help to bridge the skill gap that exists in the industry and academia (Hughes et al, 2011;Taylor and Hooley, 2014;Abrahamson et al, 2016;Agarwal et al, 2019). Some researchers have identified essential skills required by the industry for MBA graduates (Benson et al, 2014;Ayoubi et al, 2017). Several studies have also examined the cause of the skill gap in MBA education programmes of B-schools in India (Pandiyan, 2011;Bansal and Agarwal, 2019;Bhatia and Panneer, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reason for these required skills is that employees in these countries generally stay in their job for a long period because job security is regarded as very important, whereas employers from developed economies expect their employees to have a global mindset, accept diversity, work with people from various backgrounds (Andrews and Higson, 2008;Mitchell et al, 2010;Zaharim et al, 2009) and be socially responsible (Jackson, 2013a;Robles, 2012), because global mobility among workers is observed more in developed than in emerging economies. Ayoubi et al (2017) studied the views of business executives on employability skills requirements in Syria and concluded that employers in Syria are less likely to regard social skills as important in comparison with employers from developed countries like Australia and the UK.…”
Section: Employability Skills In Emerging Economiesmentioning
confidence: 99%